2014
DOI: 10.2174/1871527313666140612103425
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress But Not Exercise Increases Cortisol and Reduces State Anxiety Levels in School Classes - Results from a Stressor Applicable in Large Group Settings

Abstract: Both, psychosocial stress and exercise in the past have been used as stressors to elevate saliva cortisol and change state anxiety levels. In the present study, high-school students at the age of 14 were randomly assigned to three experimental groups: (1) an exercise group (n = 18), that was running 15 minutes at a medium intensity level of 65-75% HRmax, (2) a psychosocial stress group (n = 19), and (3) a control group (n = 18). The psychosocial stress was induced to the students by completing a standardized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Participants did not receive financial compensation for participation. Findings of this study, but not related to the power motive, were previously reported [22,33,34].…”
Section: Participantscontrasting
confidence: 60%
See 4 more Smart Citations
“…Participants did not receive financial compensation for participation. Findings of this study, but not related to the power motive, were previously reported [22,33,34].…”
Section: Participantscontrasting
confidence: 60%
“…In the school setting we used, participants with a high implicit power motive showed significantly increased salivary cortisol responses to a psychosocial stressor that only announced social evaluation. This pattern of results can be expected in situations that are unpredictable, uncontrollable, and socio-evaluative for the participants [4,22]. In our study, the results were additionally independent of the actual outcome of the test situation, meaning students did not know whether they performed well or badly in the test.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations